Karakteristik Perawat Pelaksana terhadap Perilaku Caring - Kristianingsih Kristianingsih; Fitri Arofiati; Giri Widakdo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between the characteristics of the implementing nurse on Watson's caring behavior at Bhayangkara Hospital Tk I R. Said Sukanto. The research method is descriptive-analytic with a cross-sectional approach. The results showed that caring behavior was influenced by years of service (p = 0.002) OR = 7.167. Multivariate results obtained that the variables significantly related to caring behavior were years of service, which were controlled by confounding, namely age and marital status. The model formed is declared feasible because it meets the model's meaning seen from the Omnibus test value (p = 0.000). Based on the Nagelkerke R Square value = 0.384, the independent variables contained in the model (length of work, age, marital status) can explain caring behavior by 38.4%. In conclusion, the working period is the dominant factor in caring behavior. Keywords: Characteristics of Nurses, Caring Behavior, Implementing Nurses